A summary and appraisal of existing evidence of antimicrobial resistance in the Syrian conflict. (October 2018) - Abbara, Aula; Rawson, Timothy M.; Karah, Nabil; El-Amin, Wael; Hatcher, James; Tajaldin, Bachir; Dar, Osman; Dewachi, Omar; Abu Sitta, Ghassan; Uhlin, Bernt Eric; Sparrow, Annie
Abstract: Antimicrobial resistance (AMR) in populations experiencing war has yet to be addressed, despite the abundance of contemporary conflicts and the protracted nature of twenty-first century wars, in combination with growing global concern over conflict-associated bacterial pathogens. The example of the Syrian conflict is used to explore the feasibility of using existing global policies on AMR in conditions of extreme conflict. The available literature on AMR and prescribing behaviour in Syria before and since the onset of the conflict in March 2011 was identified. Overall, there is a paucity of rigorous data before and since the onset of conflict in Syria to contextualize the burden of AMR. However, post onset of the conflict, an increasing number of studies conducted in neighbouring countries and Europe have reported AMR in Syrian refugees. High rates of multidrug resistance, particularly Gram-negative organisms, have been noted amongst Syrian refugees when compared with local populations. Conflict impedes many of the safeguards against AMR, creates new drivers, and exacerbates existing ones. Given the apparently high rates of AMR in Syria, in neighbouring countries hosting refugees, and in European countries providing asylum, this requires the World Health Organization and other global health institutions to address the causes, costs, and future considerations of conflict-related AMR as an issue of global governance.